The complete mitochondrial genome of Acanthosaura lepidogaster (Squamata: Agamidae). (4th March 2017) - Yu, Xiu-Li; Du, Yu; Yao, Yun-Tao; Lin, Chi-Xian; Lin, Long-Hui
Abstract: In this paper, we report the complete mitochondrial genome of Acanthosaura lepidogaster (Squamata, Agamidae), which is a circular molecule of 16 899 bp in size and consists of 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a control region. The overall base composition is as follows: T (22.8%), C (30.5%), A (32.3%), and G (14.4%). We constructed a phylogeny that included for 10 species of Leiolepidinae lizards and one outgroup Leiocephalus personatus constructed in BEAST, based on 15 mitochondrial genes ( 12S, 16S, ND1, ND2, COI, COII, ATP8, ATP6, COIII, ND3, ND4L, ND4, ND5, ND6, and cytochrome b ). The topology of the phylogenetic tree is broadly similar to that mentioned by Pyron et al.